Pre-modern English Identity and Roman Otherness in Shakespeare’s Cymbeline: Some Gender-based Considerations - Puchmüller, Andrea Bibiana (Íkala, Revista de Lenguaje y Cultura, 2020)
This paper aims at characterizing Shakespeare’s Cymbeline relying upon some aspects featured by Shakespearean Roman history genre, as those reveal various tensions between the English premodern identity and the Roman ethos, which was considered an imperialist model by Jacobean and Elizabethan England. This analysis is carried out from a revisionist historical perspective of premodern England, and from the idiosyncratic framework of Shakespearean Roman history plays. It is concluded that Cymbeline displays an ironic dialectics between the double canon of Roman ethos, romanitas and pietas, positioning it as contradictory and detrimental for the social health of the body politics. Shakespeare’s Rome in Cymbeline represents the contrary to the idealized model used by Elizabethan imperial propaganda in the process of construction of their national poiesis.